Pneumatic Formwork as an Effective Method for Constructing Underground Structures - Shpakova, H.; Prokopenko, D. (Ways to Improve Construction Efficiency, 2024)
In modern underground construction, one of the key directions is the implementation of innovative technologies that significantly enhance the efficiency of building projects, reduce time costs, and ensure high-quality structures. One such technology is pneumatic formwork, which opens up new possibilities for the construction of various underground facilities. This technology, which involves using a durable membrane shell filled with air under high pressure, can be adapted for constructing different types of underground structures. Pneumatic formwork can be particularly effective in the construction of subway tunnels, one of the most complex and labor-intensive underground projects. It enables a significant reduction in the time required for formwork installation and improves the technical and economic efficiency of building shallow-depth tunnels. Additionally, pneumatic formwork has great potential for use in the construction of other underground structures, such as bomb shelters, protective shelters, storage rooms, underground power stations, and drinking water reservoirs. The application of pneumatic formwork is particularly promising in the construction of shallow-depth metro tunnels, where the specific structural requirements and constraints of the construction process demand the use of compact and rapid manufacturing and installation technologies. One of the main advantages of this technology is its ability to quickly adapt to various project requirements, including the shape and size of the structure. Pneumatic formworks can be produced in various shapes and sizes, depending on the specific needs of the underground facility. This flexibility allows for the construction of not only tunnels but also other essential infrastructure projects, from civil shelters to critical infrastructure facilities. The purpose of this article is to explore the potential use of pneumatic formwork in the construction of various underground facilities, such as metro tunnels, bomb shelters, protective shelters, and other infrastructure projects, as well as to assess its technical advantages and potential in the context of modern challenges.